Palavra, silêncio, escritura: a mística de um currículo a caminho da contemplação - Silva, Maurina Passos Goulart Oliveira da (2008)
This paper presents the analysis of different experiences conducted by GEPI in two brazilian regions, Porto Velho (North) and Cachoeira do Sul (RS), aside from classroom accounts from the Pedagogy course and from the research group itself. It deals with an active research which, starting with a sensitive listening conducted in different itineraries covered during the professional life, aims to investigate the sense of the word and of silence in teacher education. An existential research therefore is a process which turns into a lifetime quest. The classroom is considered as being a scared place, revealer of the inner world, representing in this sense a mystic space. The search for the sense of Silence and the Word, in practice analysis starting from the itinerances of the diverse covered paths, has pointed out the need of a interdisciplinary approach which brings together different study areas such as: education, religion, science, philosophy, literature and mystics. The analysis of the experiences from its organization until the actions and the obtained results (what was thought, and what was experienced) constitutes the investigation of an educational program in action. These analysis indicated the needful cultivation of the inner life that touches God towards a formation which develops sensitvity and spirituality as a foundation of a more humane education. At the end of the path we conclude that a spiritual rather than a intellectual education raises questions not only about professional practice, but also about the educational program, because in this sense, it becomes necessary to conceive a program directed towards contemplation